The Effect of Analogy Strategy in Teaching Science on Achievement and Development of Creative Thinking Skills of the First Grade Intermediate Female Students - Ziyad, Haleema Sulieman Abdullah (Journal of Educational and Psychological Sciences, 2020)
The research aimed to know The Effect of The Analogies Strategy in The Teaching of Science on Achievement and The Development of Creative Thinking Skills of The First Grade Intermediate Female Students, To achieve the aim of the research, the approach was used experimental; it was chosen as the experimental design for the two experimental and control group with the test after- behind, where the researcher prepared a test in the Achievement and The Creative Thinking Skills, was chosen as a random sample numbered (60) Student, the students of The First Grade Intermediate Female Students in Abha, Asir Province, has been divided into two groups: experimental numbered (30) student, studied using the Analogy strategy, and an officer numbered (30) students, studied using the usual way, it has been applied to the experience during the first semester of the academic year 1436/1437 AH. At the end of the experiment was applied the both two tests on the two groups, has resulted in the search for and no statistically significant differences at the level of results (0.05) between the mean scores of students in the experimental group (which studied using Analogy strategy) and control group (studied using usual) way, in the post application to test the Achievement and testing of Creative thinking skills for the experimental group. Also, it found that the use of Analogy strategy in the teaching of science has had a significant impact on the achievement and Achievement and The Development of Creative Thinking Skills of The First Grade Intermediate Female Students. In the light of the results, the study recommended to ensure that science teachers use the strategy of analogies in teaching because of its impact in achieving the desired goals, and increase the cultural awareness of science teachers about the topic of innovative thinking and the importance of its development among their students, and I also proposed conducting a study of the impact of science education using the analogies strategy on developing other skills of thinking.